Analysis of Pre-service TeacherÃ¢â¬â¢s Understanding Chemical Concept In Project Based Learnig Based On Critical Thinking Disposition - Yayuk Andayani; Hasnawati Hasnawati; Saprizal Hadisaputra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This research is an Ex Post Facto research aims to analyze understanding of concept pre-service teacherÃ¢â¬â¢s that learns using project based learning (PjBL) based on critical thinking disposition (CTD). The research subject is chemistry pre-service teacherÃ¢â¬â¢s, Mataram University whose programmed Physics Chemistry 3 Course.. The variables consist of attribute variable are PjBL and CTD and dependent variable is understanding of concept. CTD data obtained through critical thinking disposition instrumen and content knowledge data obtained through multiple choice three tier test. The results of the analysis show that the level of understanding of the concept of the students with the category of understanding the concept well has a higher percentage for the high positive CTD group than the low positive KcBK group with the percentage 64.6% and 55.56% respectively. Further analysis results of each material obtained the percentage of understanding the concept correctly highest on photochemical material (62.5%) and lowest on ireversible process material (58.33%). Based on the analysis result, it is concluded that the level of understanding of chemistry concept of high positive CTD group is better than the low positive CTD group and PjBL is able to facilitate prospective teachers to understand the concept